Fundamentals of home wound care caring for the pressure ulcer patient (Philadelphia : Lipincott, 1995)
(Producer) Provides information on the following: the skin and its functions, the three phases of the healing process, risk factors for pressure ulcers, wound assessment, and documentation.
Videocassettes is available at Koleksi Media Perpustakaan HUKM
Keywords: Veins -- pathology -- atlases -- videocassettes; Phlebitis -- atlases -- videocassettes; Varicose Veins -- atlases -- videocassettes; Venous Insufficiency -- atlases -- videocassettes